2009
DOI: 10.1292/jvms.71.583
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of the S1 Gene of 4/91 Type Infectious Bronchitis Virus Isolated in Japan

Abstract: ABSTRACT. S1 gene sequences for infectious bronchitis virus (IBV) strains of the 4/91 genotype (commonly called 793B) isolated from field outbreaks in Japan were analyzed to ascertain the relationship to 4/91 vaccine strain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…Three amino acids at positions 95, 508 and 530 were different between a UK/4/91 field isolate (4/91 pathogenic) and its embryo-passaged, attenuated derivative (4/91 vaccine) (Cavanagh et al, 2005). Interestingly, TA03 shared the same three amino acids with the 4/91 pathogenic strain, even though these changes are not associated with pathogenicity (Shimazaki et al, 2009). It has been suggested that replication of 4/91 strains in chickens and embryonated eggs is associated with position 95, particularly alanine in the vaccine strain and serine in the chickpassaged strain (Cavanagh et al, 2005).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Three amino acids at positions 95, 508 and 530 were different between a UK/4/91 field isolate (4/91 pathogenic) and its embryo-passaged, attenuated derivative (4/91 vaccine) (Cavanagh et al, 2005). Interestingly, TA03 shared the same three amino acids with the 4/91 pathogenic strain, even though these changes are not associated with pathogenicity (Shimazaki et al, 2009). It has been suggested that replication of 4/91 strains in chickens and embryonated eggs is associated with position 95, particularly alanine in the vaccine strain and serine in the chickpassaged strain (Cavanagh et al, 2005).…”
Section: Discussionmentioning
confidence: 98%
“…The spreading of a virus from one area to another could be due, at least in part, by the illegal trading of chickens or by the use of attenuated vaccines. Recently, wild birds have been of concern as natural IBV carriers, since infected birds carry the viruses from one area to another (Cavanagh, 2007;Liu et al, 2005;Shimazaki et al, 2009;Sun et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The values with different letters are significantly different (P<0.05) (Cavanagh 2003(Cavanagh , 2007Kameka et al 2014). However, the emergence of new IBV variants, which led to infectious bronchitis outbreaks in vaccinated flocks, resulted in significant production losses (Xu et al 2007;Shimazaki et al 2009;Kameka et al 2014). Therefore, a novel approach that could be used as an alternative to, or in addition to, the existing means of control is urgently needed.…”
Section: Avbd5mentioning
confidence: 99%
“…These vaccines use IBV strains such as Massachusetts, Connecticut and Arkansas and combinations thereof providing protection against almost all field strains of IBV. However, emergence of new variant more heterogeneous IBV strains (Cavanagh, 2003), leads to infectious bronchitis outbreaks in vaccinated flocks leading to significant production losses (Shimazaki et al, 2009;Xu et al, 2007). Therefore a novel approach that could be used as an alternative or additional to the existing means of control is urgently needed.…”
Section: Introductionmentioning
confidence: 99%